Efficacy of Bedside Index for Severity In Acute Pancreatitis (Bisap) Score As Predictor of In-Hospital Outcome in Acute Pancreatitis (Bangladesh Journal of Medicine, 2024)
Background: Acute pancreatitis is a potentially life-threatening condition characterized by inflammation of the pancreas. Early identification of patients at risk of severe disease is crucial for devising appropriate management strategies and improving outcomes. The aim of the study was to investigate the efficacy of BISAP score as predictor of in-hospital outcome in patients with acute pancreatitis. Methods: This was a longitudinal study conducted in Department of Medicine, Sir Salimullah Medical College Mitford Hospital, Dhaka from January 2023 to December 2023. After ethical approval, a total 107 subjects were included in this study based on inclusion and exclusion criteria. Severity of the disease was assessed by BISAP score. Theoutcome determinants were length of hospital stay, complete recovery, partial recovery with complication, transfer to ICU and mortality. Chi Square test, Binominal Regression analysis and Receiver operator characteristic (ROC) curve analysis were performed as applicable. p value